Engineered CD4 T cells expressing a membrane anchored viral inhibitor restrict HIV-1 through cis and trans mechanisms - Wang, Weiming; Truong, Khanghy; Ye, Chaobaihui; Sharma, Suman; He, Huan; Liu, Lihong; Wen, Michael; Misra, Anisha; Zhou, Paul; Kimata, Jason T. (Frontiers in Immunology, 2023)
HIV-1 infection of target cells can occur through either cell-free virions or cell-cell transmission in a virological synapse, with the latter mechanism of infection reported to be 100-to 1,000-fold more efficient. Neutralizing antibodies and entry inhibitors effectively block cell-free HIV-1, but with few exceptions, they display much less inhibitory activity against cell-mediated HIV-1 transmission. Previously, we showed that engineering HIV-1 target cells by genetically linking single-chain variable fragments (scFvs) of antibodies to glycosyl phosphatidylinositol (GPI) potently blocks infection by cell-free virions and cell-mediated infection by immature dendritic cell (iDC)-captured HIV-1. Expression of scFvs on CD4 + cell lines by transduction with X5 derived anti-HIV-1 Env antibody linked to a GPI attachment signal directs GPI-anchored scFvs into lipid rafts of the plasma membrane. In this study, we further characterize the effect of GPI-scFv X5 on cell-cell HIV-1 transmission from DCs to target cells. We report that expression of GPI-scFv X5 in transduced CD4 + cell lines and human primary CD4 + T cells potently restricts viral replication in iDC-or mDC-captured HIV-1 in trans. Using live-cell imaging, we observed that when GPI-GFP or GPI-scFv X5 transduced T cells are cocultured with iDCs, GPI-anchored proteins enrich in contact zones and subsequently migrate from T cells into DCs, suggesting that transferred GPI-scFv X5 interferes with HIV-1 infection of iDCs. We conclude that GPI-scFv X5 on the surface of transduced CD4 + T cells not only potently blocks cellmediated infection by DCs, but it transfers from transduced cells to the surface of iDCs and neutralizes HIV-1 replication in iDCs. Our findings have important implications for HIV-1 antibody-based immunotherapies as they demonstrate a viral inhibitory effect that extends beyond the transduced CD4+ T cells to iDCs which can enhance HIV-1 replication.